ANALISIS PENGARUH PEUBAHAN ARUS KAS DAN LABA AKUNTANSI TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) (Tahun 2018-2020) - Linda Devita; M. Cholid Mawardi; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2021)
This study aims to determine whether cash flow information and accounting profit affect an investor in making investment decisions seen from the stock returns that will be obtained. Where this study also uses independent variables, namely operating cash flow, investment cash flow, funding cash flow and accounting profit. This study uses multiple linear regression analysis. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020 which were carried out on 135 manufacturing companies. The results of the research on investment cash flow have a significant effect on stock returns and accounting earnings have a significant effect on stock returns. This indicates that investment cash flow information and accounting profit are considered in the disclosure of annual reports for investors in making decisions. And the other independent variables are not proven to have a significant effect on stock returns.Keywords: cash flow, accounting profit, stock returns and investment decisions.